Male Embryos Produced in vitro Deviate From Their in vivo Counterparts in Placental Gene Expression on Day 32 of Pregnancy - Drum, Jéssica N.; Madureira, Guilherme; Rosa, Camila O.; Seneda, Marcelo M.; Wiltbank, Milo C.; Sartori, Roberto; Ortega, M. Sofia (Frontiers in Animal Science, 2022)
This study compared the gene expression of extraembryonic membranes (EEM) from in vitro produced (IVP) and in vivo (AI) derived pregnancies. A piece of conceptus (day 18) or chorioallantois (day 32) was used for DNA and RNA isolation and sex determination. Male and female ratios were analyzed by Chi-square. A total of three samples per sex and group (AI and IVP, days 18 and 32) were used for transcriptome analysis. Differentially expressed genes (DEGs) were determined using edgeR-robust. A false discovery rate (FDR) <0.05 was used for statistical significance. Sex ratio was similar on day 18 for AI and IVP groups. On day 32, the IVP group had a greater number of females than males (75 vs 25%, P=0.004). On day 18 female conceptuses, 50 genes were upregulated in IVP, and 21 in AI. IGF2, which is involved in placenta development, and APOA2, APOB, and APOE, involved in lipid metabolism, were upregulated in IVP conceptuses. On day 18, males had 15 upregulated genes in AI and 7 in IVP. On day 32, females had 21 upregulated genes in AI and 53 in IVP. Genes involved in lipid synthesis and metabolism were increased in the IVP group. Males on day 32 presented 899 DEGs, 564 upregulated in AI and 335 in IVP. Embryos from IVP had decreased expression of genes related to lipid and carbohydrate metabolism. Interestingly, pregnancy-associated glycoproteins (PAG) 7, 9, 10, and 19, were downregulated in IVP male. When comparing IVP males and females, 3091 genes were upregulated in females, and 3662 in male on day 18. Genes upregulated in females were related to placental function such as PLAC8A and PAGs 6, 8, 10, 12, 17, 18 and 19. On males, IFNT-related genes were upregulated. On day d32, 3252 genes were increased in females, and 3520 in male placentas. Genes increased in female placentas were: PAGs 17, 19, 9 and PLAC8B. In conclusion, IVP-derived male embryos were more susceptible to alterations in gene expression and these effects extend to the peri-implantation period including genes associated with placental development and markers of placental function.